2019
DOI: 10.1038/s41562-019-0734-z
|View full text |Cite
|
Sign up to set email alerts
|

Universal norm psychology leads to societal diversity in prosocial behaviour and development

Abstract: Recent work has proposed that social norms play a key role in motivating human cooperation, and in explaining the unique scale and cultural diversity of our prosociality. However, there has been little work directly linking social norms to the form, development, and variation in prosocial behavior across societies. In a cross-cultural study of eight diverse societies, we provide evidence that (1) adults' prosocial behavior is predicted by what other members of their society judge to be the correct social norm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
180
3
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(199 citation statements)
references
References 46 publications
(65 reference statements)
5
180
3
11
Order By: Relevance
“…voluntary actions that benefit another individual at no or low costs to the actor; Marshall-Pescini et al, 2016 ), is of particular interest from an evolutionary point of view, because the act of benefitting another individual without receiving a direct gain to oneself represents an evolutionary puzzle ( Clutton-Brock, 2009 ; Riehl, 2013 ). Humans show high levels of prosocial behaviors from an early age on ( Silk and House, 2011 ), although their expression and developmental trajectories are subject to cross-cultural and societal variation ( House et al, 2020 ). The importance of prosociality for human interactions has inspired comparative studies on the evolutionary origin of this trait.…”
Section: Introductionmentioning
confidence: 99%
“…voluntary actions that benefit another individual at no or low costs to the actor; Marshall-Pescini et al, 2016 ), is of particular interest from an evolutionary point of view, because the act of benefitting another individual without receiving a direct gain to oneself represents an evolutionary puzzle ( Clutton-Brock, 2009 ; Riehl, 2013 ). Humans show high levels of prosocial behaviors from an early age on ( Silk and House, 2011 ), although their expression and developmental trajectories are subject to cross-cultural and societal variation ( House et al, 2020 ). The importance of prosociality for human interactions has inspired comparative studies on the evolutionary origin of this trait.…”
Section: Introductionmentioning
confidence: 99%
“…industrialized, rich and democratic) populations [1] has given way to intensified research funding, publication and visibility of collaborative cross-cultural studies across the social sciences that expand the geographical range of study populations (e.g. [2][3][4][5][6][7][8][9][10]). The rapid expansion of cross-cultural team science has been precipitated by the ever-increasing availability of online global data sources and the expansion of the cross-cultural enterprise into fields such as economics [11], political science [12] and other disciplines with little previous field research expectations or ethnographic focus.…”
mentioning
confidence: 99%
“…Twenty participants from secondary schools (ages [14][15][16] were excluded due to technical problems with saving the learning data. Four participants were excluded because they did not finish the cognitive behavioural measures, and therefore IQ could not be estimated.…”
Section: Participantsmentioning
confidence: 99%
“…Developmental research into social decision-making has shown that from an early age, children trust others and recognize that investing in others can lead to mutual benefits 11 . Cooperative behaviours, such as trust and prosocial behaviour, are thought to continuously increase during adolescence 5,[12][13][14] (but see 15 ). A more nuanced view is that adolescents do not show more cooperative behaviours per se, but instead increasingly tailor their behaviour to the social environment.…”
Section: Introductionmentioning
confidence: 99%